1899
DOI: 10.5962/bhl.title.8977
|View full text |Cite
|
Sign up to set email alerts
|

A monograph of the coleopterous families Corylophidae and Sphaeriidae

Abstract: The Species found iu America are thus distriljuted : -America-Northern 15 Central Corylophus Peruanus.-Breviterovalis, glaber. l;evis, niger, prothorace antico pedibusqne testaceis, prothorace antice rotundato, margine paullo (lateraliter magis) deplanato; coleopteris apice rotundatis, lateribus margiuatis.Long. IJ ; lat. 1 mill. -Broader than C. cassidoides, black, shining, front of thorax and legs yellow, thorax semicircular, with the margins slightly reflesed, posterior angles acute, elytra moderately conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

1978
1978
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 0 publications
1
21
0
Order By: Relevance
“…Although proliferative activity as indicated by presence and number of Ki-67* cells was scored in a rather crude way, the present data compare well with those obtained by more sophisticated methods. As far as the various cysts are concerned, an increased proliferative activity for OKC in comparison with DC and RC has been a consistent finding (1,(3)(4)(5)(6) and is in agreement with the clinical behaviour of OKC. In the case of AB the variation in numbers of proliferating cells is comparable with previous data (8).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Although proliferative activity as indicated by presence and number of Ki-67* cells was scored in a rather crude way, the present data compare well with those obtained by more sophisticated methods. As far as the various cysts are concerned, an increased proliferative activity for OKC in comparison with DC and RC has been a consistent finding (1,(3)(4)(5)(6) and is in agreement with the clinical behaviour of OKC. In the case of AB the variation in numbers of proliferating cells is comparable with previous data (8).…”
Section: Discussionsupporting
confidence: 75%
“…Accepted for publication May 15, 1995 The general acceptance that increased cell proliferation plays a role in the development of odontogenic cysts and tumors is based upon a variety of reports using different methods to study proliferative activity including counting mitoses, immunohistochemical demonstration of proliferation markers and in vitro studies using autoradiography (1)(2)(3)(4)(5)(6)(7)(8), Also, several studies have indicated differences in expression of growth factor receptors which may be important in the pathogenesis of odontogenic cysts and tumors (9,10), A possible cuase of increased cell proliferation may be a mutation of the p53 gene. In normal cells, p53 is a negative regulator of cell division and inactivation of this gene is one of the most common genetic changes in human cancer (11), Changes of the p53 gene result in a gene product (p53 protein: p53P) which has an increased half-life in comparison with the wild-type protein.…”
mentioning
confidence: 99%
“…The nature of such stimuli is unclear, but it is interesting that the secretory matrix proteins of normal odontogenic epithelium have been reported to be chemotactic to mast cells (18). Although odontogenic cysts are not known to secrete enamel matrix proteins, the epithelial lining stains positively for keratins (19)(20)(21) and keratins have been shown to share common antigenie determinants with enamel matrix proteins (22).…”
Section: Discussionmentioning
confidence: 99%
“…The bracketed term containing the viscosity ratio, K , strictly applies only for creeping flow"", but is used Taken together, Equations ( 5 ) and ( 6 ) set a lower limit on the maximum stable diameter, (d,),,,, given by (7) From Equation ( 4 ) , a disturbance which originated on the axis of symmetry would never reach the equator. A reasonable approach"" is to consider disturbances with a node a t the nose, i.e.…”
Section: Theoretical Modelmentioning
confidence: 99%